Pengaruh Kebugaran Jasmani Dengan Produktivitas Individu di Era Industri 4.0 - Sirilus Daniel Agung Syawang; Feri Ilham Azkia; Ikrom Bahari; Jasmine Nur Syamsina; Darrell Hammam Luthfiadi; Anindya Nurshadrina Ramadhani; Agus Mulyana (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
In the context of the Industrial Era 4.0, which is characterized by the rapid development of digital technology and automation, consideration of individual physical fitness is becoming increasingly important. Physical health and fitness have a major impact on personal productivity in an ever-changing, digitally connected work environment. This article examines the relationship between fitness fitness and personal productivity during this period. Empirical studies and research literature support the assumption that fitness has a positive impact on individual productivity. People who maintain physical health tend to have higher energy levels, better stress tolerance, and better cognitive abilities. These factors are becoming increasingly important in a competitive, technology-driven work environment. However, there are challenges to implementing this concept effectively in the Industrial Era 4.0. Changes in work patterns, time pressures and the tendency to be attached to digital devices can hinder maintaining physical fitness. Therefore, organizations and individuals need to adopt a holistic approach, including healthy lifestyle habits, smart planning, and the use of technology to support work-life balance. Understanding the relationship between physical fitness and personal productivity in the Industry 4.0 Era allows companies to take proactive steps to improve the health and well-being of their employees, resulting in improved overall company performance and competitiveness.